A role for small ruminants in sustainable cropping systems in the humid zone of West Africa - Sumberg, J.E.; Okali, C.; Carew, B.A.R. (International Livestock Centre for Africa, 1982)
Discusses ILCA's research programme on integrating goat & sheep production into alley cropping systems i.e. production of crops between permanent rows of intensively managed trees, and also crop & animal production constraints inherent in the humid zones of West Africa and outlines on-going alley cropping trials on cut-and-carry browse feeding or direct grazing of trees during fallow periods.